ANALISIS BUDAYA ORGANISASI SEBAGAI MEDIATING VARIABEL TERHADAP HUBUNGAN SAFETY CLIMATE DENGAN ORGANIZATIONAL CITIZENSHIP BEHAVIOUR PERAWAT - Anita Syarifah; Rahmi Fahmi; Dorisnita Dorisnita (Jurnal Ilmiah Permas: Jurnal Ilmiah STIKES Kendal, 2019)
Citizenhip Organizational behavior (OCB) is a free behavior of individuals that are explicitly or indirectly recognized by the formal system and in the aggregate with affective and efficient functioning within an organization. With the increase organizational behavior citizenhip the nurse is able to do his work outside his job description. This study aims to know the culture of the organization as a mediating variable in the relationship with the organizational safety climate behavior citizenhip nurse. This research design correlation analysis, cross-sectional approach. Samples were 182 nurses with propposional random sampling. The research result is organizational culture nurses with an average of 4,22 categorized as excellent, nurse safety climate with an average of 4.00 considered good, organizational behavior citizenhip nurses with an average of 4.06 considered good. There is a relationship with the organizational safety climate citizenhip nurse behavior and organizational culture as a mediating variable of 47.3% in patient wards Arifin Achmad Pekanbaru. Suggestions for installation pelayanana is a need for supportive management of safety climate and soft skill training to improve organizational behavior citizenhip nurse